Omega-3 Fatty Acid Supplementation and Cardiovascular Disease - Jump, Donald B.; Depner, Christopher M.; Tripathy, Sasmita
Epidemiological studies on Greenland Inuits in the 1970s and subsequent human studies have established an inverse relationship between the ingestion of omega-3 fatty acids [C₂₀₋₂₂ ω3 polyunsaturated fatty acids (PUFA)], blood levels of C₂₀₋₂₂ ω3 PUFA and mortality associated with cardiovascular disease [CVD]. C₂₀₋₂₂ ω3 PUFA have pleiotropic effects on cell function and regulate multiple pathways controlling blood lipids, inflammatory factors and cellular events in cardiomyocytes and vascular endothelial cells. The hypolipemic, anti-inflammatory, anti-arrhythmic properties of these fatty acids confer cardioprotection. Accordingly, national heart associations and government agencies have recommended increased consumption of fatty fish or ω3 PUFA supplements to prevent CVD. In addition to fatty fish, additional sources of ω3 PUFA are available from plants, algae and yeast. A key question examined in this review is whether non-fish sources of ω3 PUFA are as effective as fatty fish-derived C₂₀₋₂₂ ω3 PUFA at managing risk factors linked to CVD. We have focused on ω3 PUFA metabolism and the capacity of ω3 PUFA supplements to regulate key cellular events linked to CVD. The outcome of our analysis reveals that non-fish sources of ω3 PUFA vary in their capacity to regulate blood levels of C₂₀₋₂₂ ω3 PUFA and CVD risk factors. Keywords: Dyslipidemia, Inflammation, Cardiomyocyte, Single nucleotide polymorphism, Endothelial cell, PUFA metabolism Keywords: Dyslipidemia, Inflammation, Cardiomyocyte, Single nucleotide polymorphism, Endothelial cell, PUFA metabolism